2009
DOI: 10.1177/0891242408327708
|View full text |Cite
|
Sign up to set email alerts
|

Is Local Discretionary Sales Tax Adopted to Counteract Fiscal Stress?

Abstract: Economic development has traditionally relied on operational resources concentrated in the government's general fund balance for postinfrastructure operations. In this article, the authors explore the phenomenon of infrastructure surtax adoption for development and operation in an empirical analysis of Florida counties. The authors focus their analysis on the factors that influence the adoption grounding the analysis in the theoretical framework of the policy innovation and adoption literature. Their results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…When counties lack a competitive nature or the ability to compete, they lack the incentive to strive for effi ciency and fi scal health. A number of recent studies have demonstrated the competitive drive of local governments with the diff usion of policies (see Kim, Bae, and Eger 2009;McDonald and Gabrini 2014). As neighboring governments adopt policies that prove successful, local governments must either follow suit or face decline.…”
Section: A County Charter As Competitionmentioning
confidence: 99%
“…When counties lack a competitive nature or the ability to compete, they lack the incentive to strive for effi ciency and fi scal health. A number of recent studies have demonstrated the competitive drive of local governments with the diff usion of policies (see Kim, Bae, and Eger 2009;McDonald and Gabrini 2014). As neighboring governments adopt policies that prove successful, local governments must either follow suit or face decline.…”
Section: A County Charter As Competitionmentioning
confidence: 99%
“…Where the effect of a surtax differs is in its indirect effects. As an additional tax, the implementation and revenue use of a surtax are carefully established (Kim, Bae, and Eger 2009). Levied funds have a predetermined purpose, often one that is redistributive in nature, and the tax burden is designed to target certain segments of the population.…”
Section: A Theory Of Surtaxesmentioning
confidence: 99%
“…The Tiebout hypothesis suggests that households will relocate to a jurisdiction where the set of goods, services and taxes matches their preferences (Tiebout 1956). A number of studies have shown the diffusion of government policies at the county level, including two that deal specifically with Florida (see Kim, Bae, and Eger 2009;McDonald and Gabrini 2014), have virtually no effect on household relocation. These studies suggest that households who move might receive a temporary benefit from reduced taxation, but the new jurisdiction is likely to adopt a tax similar to those of the household's previous residence.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…They find that with an additional dollar of earmarked taxes for highways, there is only a $0.19 increase in highway spending. 13 Kim, Bae, and Eger (2009) use per capita income as a measure for infrastructure demand and find that increases do not bring greater demand for an infrastructure tax. These findings suggest that earmarked revenue is spent in a manner reflective of the rational model and that tax earmarks are not distortionary.…”
Section: Rational Modelmentioning
confidence: 99%